PENINGKATAN KUALITAS PEMBELAJARAN GEOMETRI BERDASARKAN TEORI VAN HIELE MELALUI MODEL INKUIRI - Stiawan, Nursiwi Nugraheni, Sumilah, Agus (Joyful Learning Journal, 2015)
Penelitian ini bertujuan meningkatkan kualitas pembelajaran geomatri. Teknik pengumpulan data menggunakan teknik tes dan nontes. Analisis data menggunakan teknik analisis deskriptif kualitatif dan kuantitatif. Hasil penelitian keterampilan guru pada siklus I memperoleh skor 25 meningkat pada siklus II menjadi 29,5, aktivitas siswa pada siklus I memperoleh jumlah skor 18,5 pada siklus II rata-rata skor 25,1, iklim pembelajaran meningkat dari siklus I jumlah skor 21 menjadi 22,5 pada siklus II, materi pembelajaran siklus I memperoleh jumlah skor 6 meningkat pada siklus II menjadi 8, media pembelajaran siklus I memperoleh jumlah skor 12 meningkat pada siklus II menjadi 14,5, kompetensi sikap spiritual dan sosial pada siklus I dan siklus II memperoleh skor modus 3 (mulai berkembang), aspek pengetahuan pada siklus I adalah 76,47% dan meningkat siklus II menjadi 97,05%. Penelitian ini membuktikan teori Van Hiele melalui model inkuiri dapat meningkatkan pembelajaran geometri di kelas IV SD Islam Hidayatullah Semarang.Ã‚Â This study aims to improve the quality of learning geomatri. Data collection techniques using test techniques and non test. The data analysis using descriptive analysis techniques of qualitative and quantitative. Results of the research skills of teachers in the first cycle to obtain a score of 25 increased in the second cycle to 29.5, the activity of students in the first cycle to obtain a total score of 18.5 in the second cycle an average score of 25.1, increasing the learning climate of the first cycle 21 total score to 22.5 in the second cycle, the first cycle of learning materials to obtain a total score of 6 is increased in the second cycle to 8, the first cycle of learning media to obtain a total score of 12 increased in the second cycle to 14.5, spiritual attitudes and social competence in the first cycle and the cycle II obtained a score of 3 mode (start growing), aspects of knowledge in the first cycle was 76.47% and increased the second cycle into 97.05%. This study proves the theory of Van Hiele through inquiry model can enhance learning in fourth grade geometry Islam Hidayatullah Semarang.